2019
DOI: 10.3390/medicina55050204
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Serum Calcium Levels on Uremic Encephalopathy in Patients with Acute Kidney Injury in the Emergency Department

Abstract: Background and objectives: Uremic encephalopathy is the most important complication of renal failure and urgent dialysis treatment is required. Parathormone (PTH) contributes to the etiopathogenesis of uremic encephalopathy. PTH is a hormone that acts in the calcium balance in the organism. The aim of our study was to investigate the effect of serum adjusted and ionized calcium on the development of uremic encephalopathy in patients with acute renal injury (acute kidney injury network (AKIN) stage 3). Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…AKI was more common in the hypocalcemic group than in the non-hypocalcemic group in patients with rhabdomyolysis [9]. In another study of ours which was a prospective study with patients with AKIN stage 3, serum calcium and ionized calcium levels of the group who received emergency hemodialysis were lower than that of those who did not undergo hemodialysis [10]. This retrospective study showed similar results.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…AKI was more common in the hypocalcemic group than in the non-hypocalcemic group in patients with rhabdomyolysis [9]. In another study of ours which was a prospective study with patients with AKIN stage 3, serum calcium and ionized calcium levels of the group who received emergency hemodialysis were lower than that of those who did not undergo hemodialysis [10]. This retrospective study showed similar results.…”
Section: Discussionsupporting
confidence: 67%
“…The findings of our study are compatible with the literature. As an exception, ionized calcium levels were found to be similar in both subgroups, the lower ionized calcium levels of group 1a patients than group 2a patients, although not reaching statistical significance, may be due to the low number of participants [10].…”
Section: Discussionmentioning
confidence: 61%
“…The mortality rate of critically ill patients with hypocalcemia was found to be as high as 50% 54 55 56) . Serum calcium concentration was inversely correlated with the severity of AKI with the lowest in the patients with uremic encephalopathy 57) . Hyperphosphatemia, parathyroid hormone (PTH) insufficiency, decreased production of renal calcitriol, sepsis, and various medications can cause hypocalcemia in critically ill patients 58) .…”
Section: Introductionmentioning
confidence: 98%